Identification of differential gene expression profile from peripheral blood cells of military pilots with hypertension by RNA sequencing analysis - Xing-Cheng Zhao; Shao-Hua Yang; Yi-Quan Yan; Xin Zhang; Lin Zhang; Bo Jiao; Shuai Jiang; Zhi-Bin Yu (BMC, 2018)
Abstract Background Elevated blood pressure is an important risk factor for cardiovascular disease and is also an important factor in global mortality. Military pilots are at high risk of cardiovascular disease because they undergo persistent noise, high mental tension, high altitude hypoxia, high acceleration and high calorie diet. Hypertension is the leading cause of cardiovascular disease in military pilots. In this study, we want to identify key genes from peripheral blood cells of military pilots with hypertension. Identification of these genes may help diagnose and control hypertension and extend flight career for military pilots. Methods We use RNA sequencing technology, bioinformatics analysis and Western blotting to identify key genes from peripheral blood cells of military pilots with hypertension. Results Our study detected 121 up-regulated genes and 623 down-regulated genes in the peripheral blood mononuclear cells (PBMCs) from hypertensive military pilots. We have also identified 8 important genes (NME4, PNPLA7, GGT5, PTGS2, IGF1R, NT5C2, ENTPD1 and PTEN), a number of gene ontology categories and biological pathways that may be associated with military pilot hypertension. Conclusions Our study may provide effective means for the prevention, diagnosis and treatment of hypertension for military pilot and extend their flight career.